Transformasi Digital Posyandu: Perancangan dan Implementasi Website untuk Meningkatkan Layanan Kesehatan Berbasis Komunitas - Rismawandi Rismawandi; Martini Martini; Agnes Aryasanti (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aims to address challenges in managing community-based health services due to fragmented manual recording practices at Posyandu Asoka RW.009 Karang Tengah, which limit data integration and reporting efficiency. The novelty of this program lies in the development of a context-specific Posyandu website tailored to the operational needs and digital readiness of cadres. The program employed a descriptive approach consisting of needs assessment, system design, development, implementation, and mentoring. Data were collected through observations, interviews, documentation, and user satisfaction questionnaires. The results show that the website improved data organization, accessibility, and reporting efficiency while reducing administrative workload. User satisfaction was very high, with an average score of 4.52 out of 5, indicating strong acceptance and perceived usefulness. In addition, the program enhanced cadres’ digital competencies and encouraged data-driven service management. Overall, this program provides an effective and replicable digital solution and highlights the importance of need-based digital interventions in improving the quality of community-based health services.